2013
DOI: 10.1175/jas-d-13-086.1
|View full text |Cite
|
Sign up to set email alerts
|

CCN and Vertical Velocity Influences on Droplet Concentrations and Supersaturations in Clean and Polluted Stratus Clouds

Abstract: Cloud microphysics and cloud condensation nuclei (CCN) measurements from two marine stratus cloud projects are presented and analyzed. Results show that the increase of cloud droplet concentrations N c with CCN concentrations N CCN rolls off for N CCN at 1% supersaturation (S)N 1% above 400 cm 23 . Moreover, at such high concentrations N c was not so well correlated with N CCN but tended to be more closely related to vertical velocity W or variations of W (s w ). This changeover from predominate N c dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 63 publications
10
64
0
Order By: Relevance
“…More water vapor is supplied to the atmosphere, which decreases the competition for water vapor between CCN activation of aerosols, resulting in more CCN and cloud droplets when there is an inversion at the top of the boundary layer (Su et al 2010;Dong et al 2015). As v increases, N c decreases, which is consistent with results reported by others (e.g., Kim et al 2008;Hudson and Noble 2014;West et al 2014). This is because the stronger ascending motion enables more of the smaller aerosols to activate as a result of the increase in maximum supersaturation (West et al 2014).…”
Section: Parameters On Cloud Propertiessupporting
confidence: 90%
“…More water vapor is supplied to the atmosphere, which decreases the competition for water vapor between CCN activation of aerosols, resulting in more CCN and cloud droplets when there is an inversion at the top of the boundary layer (Su et al 2010;Dong et al 2015). As v increases, N c decreases, which is consistent with results reported by others (e.g., Kim et al 2008;Hudson and Noble 2014;West et al 2014). This is because the stronger ascending motion enables more of the smaller aerosols to activate as a result of the increase in maximum supersaturation (West et al 2014).…”
Section: Parameters On Cloud Propertiessupporting
confidence: 90%
“…The maximum supersaturation usually remains below 0.3 % in polluted boundary-layer clouds, while higher supersaturations close to or even larger than 1 % have been reported under clean conditions and in convective clouds (Ditas et al, 2012;Hammer et al, 2014;Hudson and Noble, 2014). As discussed in Sect.…”
Section: Implications For Cloud Droplet Activationmentioning
confidence: 81%
“…The two measurement locations discussed here are interesting with regard to the ratio of presumed cloud droplet number concentration (CDNC) to the total aerosol particle number concentration. It has been reported that, although under the clean and convective conditions ambient S c may reach as high as 1.0 %, in the polluted boundary layer S c usually remains below 0.3 % (Ditas et al, 2012;Hammer et al, 2014;Hudson and Noble, 2014). If one assumes this value, a comparatively small fraction of aerosol in northern Finland and central Netherlands would potentially activate into cloud droplets if exposed to this S c .…”
Section: Ccn Concentrationsmentioning
confidence: 99%